Screening high-risk Veterans for cirrhosis: taking a stepwise population health approach - Jonathan Dounel; Carolyn Lamorte; Heather Patton; Ponni Perumalswami; Heather McCurdy; Nicole J. Kim; Lauren A. Beste; Dawn Scott; Jessimarie Casey; Patrick Spoutz; Linda Chia; Yiwen Yao; et al. (BMC Health Services Research)
Abstract Background Because cirrhosis is often unrecognized, we aimed to develop a stepwise screening algorithm for cirrhosis in the Veterans Health Administration (VHA) and assess this approach’s feasibility and acceptability. Methods VHA hepatology clinicians (“champions”) were invited to participate in a pilot program from June 2020 to October 2022. The VHA Corporate Data Warehouse was queried to identify Veterans with possible undiagnosed cirrhosis using Fibrosis-4 (FIB-4) ≥ 3.25 and at least one risk factor for liver disease (e.g., obesity), and generate an age-stratified sample. Champions at four sites reviewed charts to confirm eligibility and contacted Veterans to offer further evaluation with elastography. Feasibility was defined as protocol implementation with completion of at least one elastography test and acceptability was defined based on Veteran- and clinician-reported surveys. Participation in the program, patient outcomes, adaptations to the protocol, and implementation barriers were also assessed. Results Four sites were able to implement the screening protocol. Adaptations included type of outreach (primary care vs. hepatology, phone vs. mail) and type of elastography used. One site chose to refer patients with clear evidence of cirrhosis directly to hepatology (n = 12) rather than to elastography. Key implementation barriers included staffing, primary care provider (PCP) comfort with interpreting and communicating results, and appointment availability during the COVID-19 pandemic. Of 488 patients whose charts were reviewed, 230 were excluded from outreach based on predefined criteria (e.g., advanced cancer, prior or current referral to hepatology). Champions and PCPs attempted to contact 165 of 246 Veterans who were deemed eligible for evaluation with elastography. Among 53 Veterans who completed elastography, 22 (42%) had findings consistent with significant fibrosis and were referred to hepatology. Clinicians and Veterans reported high acceptability of the program on surveys (80% of Veterans who completed survey). Conclusions This pilot demonstrated the feasibility, acceptability, and challenges of a multisite approach to cirrhosis screening.